a. Taboo or Trivial: Women Adult Educators with Visible Tattoos and the Effect on Learners - Amanda Young (Adult Education Research Conference, 2018)
The purpose of this session is to discuss a future research project which examines the effect on adult learning conducted by a woman instructor with visible tattoos.
Keywords: Training and development; Body modification; Workplace learning; Adult education; Tattoos in the workplace